Novel heterocyclic liquid crystalline semiconductors with polymorphism. (1st December 2020) - Hu, Guang; Kitney, Stuart P.; Bao, Weixiao; Harrison, William; Lambert, Brian
ABSTRACT: Novel heterocyclic liquid crystalline semiconductors incorporating fused thiazolo[5, 4- d ]thiazole (N, S), thiophene (S), pyridine (N), and/or alkoxy (O) units have been synthesised via simple and high efficient reaction routes and exhibit polymorphic transitions. The correlation between the molecular structures, especially the presence of strong polar and electronegative heteroatoms, and mesomorphic behaviour and transition temperatures was investigated. The energy levels and band gap for heterocyclic liquid crystalline 6 and 10 have also been measured to further evaluate their potentials for use as promising organic semiconductors.